Establishment and characterization of multilayered fibroblast cell sheets from the canine oral mucosa, skin, and tail skin - Melpa Susanti Purba; Dito Anggoro; Naohiro Yamamoto; Sota Yoshimine; Junichi Murakami; Toshiki Tanaka; Kimikazu Hamano; Harumichi Itoh; Kazuhito Itamoto; Yuki Nemoto; Munekazu Nakaichi; Hiroshi Sunahara; et al. (Open Veterinary Journal)
Background: Cell sheet therapy has been developed as an effective regenerative medicine to improve wound repair treatment and prevent postoperative complications. Fibroblasts are widely used to create cell sheet engineering because of their essential role in tissue regeneration and the acceleration of the wound healing process.